A detailed methodology to model the Non Contact Tonometry: a Fluid Structure Interaction study - Redaelli, Elena; Grasa, Jorge; Calvo, Begoña; Rodriguez Matas, Jose Felix; Luraghi, Giulia (Frontiers in Bioengineering and Biotechnology, 2022)
Understanding the corneal mechanical properties has great importance in the study of corneal pathologies and the prediction of refractive surgery outcomes. Non-Contact Tonometry (NCT) is a non-invasive diagnostic tool intended to characterize the corneal tissue response in vivo by applying a defined air-pulse. The biomarkers inferred from this test can only be considered as indicators of the global biomechanical behaviour rather than the intrinsic biomechanical properties of the corneal tissue. A possibility to isolate the mechanical response of the corneal tissue is the use of an inverse finite element method, which is based on accurate and reliable modelling. Since a detailed methodology is still missing in the literature, this paper aims to construct a high-fidelity finite-element model of an idealized 3D eye for in-silico NCT. A fluid-structure interaction (FSI) simulation is developed to virtually apply a defined air-pulse to a 3D idealized eye model comprising cornea, limbus, sclera, lens and humors. Then, a sensitivity analysis is performed to examine the influence of the intraocular pressure (IOP) and the structural material parameters on three biomarkers associated with corneal deformation. The analysis reveals the requirements for the in-silico study linked to the correct reproduction of three main aspects: the air pressure over the cornea, the biomechanical properties of the tissues, and the IOP. The adoption of an FSI simulation is crucial to capture the correct air pressure profile over the cornea as a consequence of the air-jet. Regarding the parts of the eye, an anisotropic material should be used for the cornea. An important component is the sclera: the stiffer the sclera, the lower the corneal deformation due to the air-puff. Finally, the fluid-like behavior of the humors should be considered in order to account for the correct variation of the IOP during the test which will, otherwise, remain constant. The development of a strong FSI tool amenable to model coupled structures and fluids provides the basis to find the biomechanical properties of the corneal tissue in vivo.